Professores da educaç\~ao básica no Brasil: Condiç\~oes de vida, inserç\~ao no mercado de trabalho e remuneraç\~ao - Milko Matijascic (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– Life conditions for teachers working in basic education are better than those of the average Brazilian working population. However, the high number of teachers living in households with per capita income below 0.5 of the minimum wage requires attention. Teachers in public schools have better conditions than private school teachers, when controlling for teachers schooling and union representation. Nevertheless, teachers' incomes are reduced and salaries vary quite a bit throughout the country. When teachers' average salaries equal the average of the population with tertiary education, it would create conditions that would foster improved student learning.
Keywords: I25; 330; school teachers; education; income; public policies; labor market